The impact of the let-7 family on the pathophysiological mechanisms of traumatic brain injury: a systematic review - Radenza, Natalia; Mangione, Renata; Barbati, Saviana Antonella; Bellia, Francesco; Caruso, Giuseppe; Belli, Antonio; Lazzarino, Giuseppe; Tavazzi, Barbara; Lazzarino, Giacomo; Amorini, Angela Maria; Di Pietro, Valentina (Frontiers in Neurology, 2025)
Background:The lethal-7 (let-7) family of microRNAs (miRNAs) plays a crucial role in regulating key biological functions, including cell differentiation, inflammation, metabolism, and proliferation. Their dysregulation has been implicated in various diseases, including cancer and neurological disorders. Despite extensive knowledge of their roles in normal physiology and disease, the involvement of let-7 miRNAs in the pathophysiology of traumatic brain injury (TBI) remains incompletely understood.ObjectiveTo systematically identify and analyze the differential expression of let-7 family members following TBI across human and animal models and to assess their potential role as diagnostic biomarkers and therapeutic targets.MethodsA systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was retrieved from PubMed, EMBASE, and Web of Science using predefined keywords based on a PICO framework. Studies were included if they reported on let-7 family expression post-TBI in humans or animals. Risk of bias was assessed using the Evidence Project and SYRCLE tools. Data were extracted regarding species, sample type, TBI model, time points, and let-7 expression profiles. PROSPERO 2025 CRD420251129282. Available from https://www.crd.york.ac.uk/PROSPERO/view/CRD420251129282.ResultsOut of 41 initially identified records, 15 studies met the inclusion criteria. In human studies, upregulation of let-7 family members (e.g., let-7a, b, c, f, i) was consistently observed in peripheral biofluids (serum, plasma, saliva) following mild to severe TBI. However, cerebrospinal fluid (CSF) levels showed mixed or decreased expression patterns. In contrast, animal studies have shown predominant downregulation of let-7 in brain tissues post-TBI, with some evidence suggesting their role in modulating neuroinflammatory responses, apoptosis, and energy metabolism. Let-7c and let-7i were particularly implicated in the modulation of microglial activation, IL-6 regulation, and STING signaling pathways. Limited mechanistic data suggest let7′s involvement in glucose metabolism, N-acetylaspartate homeostasis, and antioxidant response.ConclusionsThe let-7 family exhibits divergent expression trends in tissue and biofluids following TBI, highlighting their potential as non-invasive biomarkers. Their regulatory roles in inflammation, metabolism, and neuroprotection suggest therapeutic promise. However, current evidence remains fragmented, and further mechanistic studies are necessary to validate their function in post-TBI recovery and to explore their utility as clinical biomarkers or treatment targets.